Empowerment Of Horticultural Peasants (Study At The Karo Regency Agriculture Service Post-Eruption Of Mount Sinabung) - Pandia, Elysa Apriliyani BR Sembiring; Muhammad Husni Thamrin (Talenta Publisher, 2022)
The eruption of Mount Sinabung impacted not only people living at the foot of volcano, but also surrounding communities. Although damage was not as severe as that experienced by displaced people, the eruption of Mount Sinabung had an influence on lives of people living in Sinabung area, particularly in agricultural sector. The agricultural production of community has diminished as a result of Mount Sinabung's eruption. Aside from lower agricultural production, lower selling prices are also a result of lower quality. This research will show how Karo Regency Agriculture Office empowers Peasants horticulture who have been impacted by Mount Sinabung's eruption. The descriptive qualitative method was employed in this study. The findings revealed that Karo Regency Agriculture Service's execution of empowerment horticultural Peasants following Mount Sinabung's eruption was still not optimal due to a number of circumstances. These factors include that Mount Sinabung is still erupting, mentality of people who have yet to accept instructor's presence, and fact that quality of extension resources is still inadequate, both in terms of expertise and field demands. The absence of field people, presence of extension workers who are members of structural posts, and a limited budget are all hurdles to horticultural Peasants’ empowerment.